Bilateral tubal ligation in a nulliparous woman – a case report. (2017)
Infertility is viewed in diverse ways in our environment with couples often attempting various options of treatment. Thus, voluntarily opting to remain childless has little or no socio-cultural approval and is often perceived to be an indication of covert disability. Commonest indication for bilateral tubal ligation (BTL) in our environment is completion of family size and in situations where further pregnancies will jeopardize maternal health. We present a case of a married 41 year old nulliparous woman who requested for BTL on religious ground. The couple had opted for voluntary childlessness and had been on other forms of contraceptives all through their twelve years of marriage. This is to highlight the fact that there exist in our society a small number of couples who wish to be childless and should not be denied that right after thorough counseling.